Corporate Governance and Financial Report Integrity: An Analysis of Independent Commissioners and Institutional Ownership - Handayani, Puspita; Febriyanto, Andi; Putri, Nabila (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2026)
Financial statement integrity is a crucial element in maintaining public trust and supporting sound economic decision-making, particularly in sectors related to essential consumer needs. However, despite the formal implementation of corporate governance mechanisms, concerns about governance effectiveness in safeguarding reporting integrity remain evident in the Indonesian capital market. This study examines how independent commissioners and institutional ownership affect financial statement integrity in consumer non-cyclical companies listed on the Indonesia Stock Exchange during 2020–2024, using agency theory and resource dependence theory. Using a quantitative approach with panel data regression, the study analyzes 145 firm-year observations and applies the Random Effects Model as the most appropriate estimation technique. The results indicate that both independent commissioners and institutional ownership have a negative and significant effect on financial statement integrity. These findings suggest that governance mechanisms may function merely as formal compliance tools rather than effective monitoring and resource-providing instruments. Independent commissioners show limited effectiveness due to inadequate involvement and insufficient financial expertise, while institutional investors prioritize short-term performance objectives that may encourage opportunistic financial reporting. This study concludes that the effectiveness of corporate governance in enhancing financial statement integrity depends not only on structural compliance but also on the quality, independence, and strategic role of governance actors, providing important implications for regulators and practitioners.